Work-related stress case definitions and prevalence rates in national surveys - Houdmont, Jonathan; Cox, Tom; Griffiths, Amanda (Oxford Journals, 2010)
Background: There is concern about lack of consistency in the design of case definitions used to measure work-related stress in national workforce surveys and the implications of this for the reliability and validity of prevalence estimates as well as for developments in policy and practice on tackling work-related stress. Aims: To examine associations between case definitions used for the measurement of work-related stress in nationally representative workforce surveys and the prevalence rates generated. Methods: The study focused on 18 nationally representative workforce surveys conducted between 1995 and 2008 that involved British samples. The published report from each survey was scrutinized for evidence of the case definition used to measure work-related stress and the associated prevalence rate. Results: Several types of case definition were identified that differed in terms of their theoretical basis, structure, and content. Each was associated with a unique range of prevalence rates. Conclusions: The results illustrate the challenge presented to the production of valid and reliable estimates of the scale of work-related stress by inconsistent case definition design. The imperative for theory-based consistency in the design of case definitions used for the measurement of work-related stress in national workforce surveys is highlighted.